The Research Progress of Host Genes and Tuberculosis Susceptibility. (14th August 2019) - Cai, Li; Li, Zhan; Guan, Xuhua; Cai, Kun; Wang, Lei; Liu, Jiafa; Tong, Yeqing
Abstract : Background/Aims . Nucleotide diversity may affect the immune regulation of tuberculosis (TB) patients, leading to the individual susceptibility to TB. In recent years, there are a lot of researches on the association of host genetic factors and TB susceptibility which has attracted increasing attention, and the in-depth study of its mechanism is gradually clear. Materials . We made a minireview on the association of many candidate genes with TB based on recent research studies systematically, such as the human leukocyte antigen (HLA) gene, the solute carrier family 11 member 1 (SLC11A1) gene system, the vitamin D receptor (VDR) gene, the mannan-binding lectin (MBL) gene, the nitric oxide synthase 2A (NOS2A) gene, the speckled 110 (SP110) gene, and the P2X7 receptor (P2X7) gene. The discovery of these candidate genes could reveal the pathogenesis of TB comprehensively and is crucial to provide scientific evidence for formulating the related measures of prevention and cure. Discussion . The host genes play important roles in the development of TB, and the host genes may become new targets for the prevention and treatment of TB. Effective regulation of host genes may help prevent or even treat TB. Conclusion . This minireview focuses on the association of host genes with the development of TB, which may supply some clues for future therapies and novel drug targets for TB.